Respostas

2013-12-01T12:33:03-02:00
Fica assim :
V = B*h
V1 = 5*π*R²
V2 = 5*π*r²
V1 - V2 = 400π
5*π*R² - 5*π*r² = 400π
5*π(R² - r²) = 400π
R² - r² = 80
R - r = 8
R = 8  + r
Agora é só substituir :
R² - r² = 80
(8  + r)² - r² = 80
64 + 16r + r² - r² = 80
16r = 80 - 64
r = 16/16 = 1
r = 1 cm
Agora vamos descobrir o R maior :
R = 8  + r
R = 8 + 1
R = 9
Sou novo aqui . Tem como aprovar a minha resposta ?! :)
3 5 3
Fica assim :
V = B*h
V1 = 5*π*R²
V2 = 5*π*r²
V1 - V2 = 400π
5*π*R² - 5*π*r² = 400π
5*π(R² - r²) = 400π
R² - r² = 80
R - r = 8
R = 8 + r
Agora é só substituir :
R² - r² = 80
(8 + r)² - r² = 80
64 + 16r + r² - r² = 80
16r = 80 - 64
r = 16/16 = 1
r = 1 cm
Agora vamos descobrir o R maior :
R = 8 + r
R = 8 + 1
R = 9
Sou novo aqui . Tem como aprovar a minha resposta ?! :)